2011
DOI: 10.3233/jpd-2011-11019
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Eye Movements are Related to Turning Performance in Parkinson Disease

Abstract: Background Persons with Parkinson disease (PD) experience difficulty turning, leading to freezing of gait and falls. We hypothesized that saccade dysfunction may relate to turning impairments, as turns are normally initiated with a saccade. Objective Determine whether saccades are impaired during turns in PD and if characteristics of the turn-initiating saccade are predictive of ensuing turn performance. Methods 23 persons with PD off medication and 19 controls performed 90 and 180 degree in-place turns to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 47 publications
8
58
0
Order By: Relevance
“…Our findings of improved turning duration and concomitant improvements in oculomotor performance during turns are novel yet anticipated based on the efficacy of DBS in improving saccade function and gait in previous studies. Previous work in our lab (Lohnes and Earhart, 2011) showed that persons with PD turn slower and with more steps than healthy, age-matched controls, and that turn performance is correlated with oculomotor function such that individuals who perform later, larger, faster, and fewer saccades turn better. Similarly, data herein suggest that improved oculomotor performance associated with DBS is correlated with improved turn performance.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Our findings of improved turning duration and concomitant improvements in oculomotor performance during turns are novel yet anticipated based on the efficacy of DBS in improving saccade function and gait in previous studies. Previous work in our lab (Lohnes and Earhart, 2011) showed that persons with PD turn slower and with more steps than healthy, age-matched controls, and that turn performance is correlated with oculomotor function such that individuals who perform later, larger, faster, and fewer saccades turn better. Similarly, data herein suggest that improved oculomotor performance associated with DBS is correlated with improved turn performance.…”
Section: Discussionmentioning
confidence: 73%
“…Such studies have noted that persons with PD require more steps and take longer to complete a turn than healthy controls (Hong et al, 2009; Lohnes and Earhart, 2011; Morris et al, 2001; Stack and Ashburn, 2008) Additionally, individuals with PD show altered timing of segmental rotations during turn initiation, such that their turning strategy is more “en bloc” than healthy controls (Crenna et al, 2007; Hong et al, 2009; Huxham et al, 2008; Visser et al, 2007), although this finding may not be observed in early PD stages (Anastasopoulos et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees in part with previous work which demonstrated an increase in horizontal saccade frequency during turns in PD (Galna et al ., ). Methodological differences however, limit comparison to other turning studies which report saccades when turning while standing in place rather than walking (Anastasopoulos et al ., ; Lohnes & Earhart, ). In contrast, their findings show that saccade frequency increases in PD compared to controls when turning.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies provided no visual outcome (saccade and fixation) definitions. Five studies (Desmurget et al, 2004, Lohnes and Earhart, 2011, Marx et al, 2012, Muilwijk et al, 2013 did provide outcome definitions, but definitions varied between studies. Twelve studies specified the VS outcome variables obtained, which often involved saccade or fixation measurements (such as saccade frequency, duration, velocity, amplitude, latency, fixation frequency and duration, Table 2).…”
Section: Outcome Measuresmentioning
confidence: 99%